New data on the genus Epipactis (Orchidaceae) in the North Caucasus with description of a new species - Fateryga, Alexander V.; Popovich, Anton V.; Fateryga, Valentina V.; Averyanova, Elena A.; Kreutz, Karel (C.a.j.) (Phytotaxa, 2018)
A new self-pollinating species, Epipactis euxina, is described from Gelendzhik District of Krasnodar Territory. The species is closely related to E. persica from which it differs by its remarkable long pedicel, distinctly longer epichile, and indistinct or absent viscidium. It grows in sparse pine forest mixed with oak, on calcareous soils. Four other taxa collected in different localities of Krasnodar Territory are new for the North Caucasus: E. krymmontana, E. leptochila subsp. leptochila, E. leptochila subsp. neglecta, and E. muelleri. A new synonymy is proposed for E. persica = E. helleborine subsp. transcaucasica. An updated key to the species of the genus Epipactis in the North Caucasus is provided. The lectotype of E. muelleri is designated.